123 ACUTE-PHASE BED-REST DURATION WAS ASSOCIATED WITH LOWER GRIP STRENGTH IN A POST-COVID-19 COHORT. (18th November 2021) - Monaghan, A; Jennings, G; Xue, F; Knight, S; Rizzo, R; Davis, J; Duggan, E; Kenny, R A; Romero-Ortuño, R
Abstract: Background: Though age-related muscle loss is traditionally associated with older cohorts, strong evidence suggests a life-spanning precipitation of decreasing muscle mass and strength beginning as early as the fourth decade of life, with established deleterious consequences for later-life morbidity and mortality. Periods of low activity and bed rest (LA/BR) can further compound this depletion of muscle strength. Our aim was to examine such associations in a post-COVID-19 cohort. Methods: Participants reporting ongoing symptomatology and fatigue post COVID-19 underwent assessments of grip strength via hand-held dynamometry (2 measures on each hand). Demographics of COVID-19 illness, including time since diagnosis, duration of LA/BR during acute illness, and levels of fatigue were captured via self-reported questionnaires. Independent predictors of mean grip strength were investigated using a linear regression model. Results: Forty-nine participants underwent assessments (69% female, mean age 44(12) years). At the time of assessment, days post COVID-19 diagnosis ranged from 39–522 (mean 262(140)). The mean self-reported period of LA/BR during the acute illness was 15(18) days. In general, participants reported significant levels of fatigue (median Chalder Fatigue Scale score 22(8)). Mean grip strength was 41.3(6.3) Kg for men and 22.8(6.7) Kg for women. When predictors of grip strength were investigated, an increased duration of LA/BR was found to be associated with lower grip strength, independently of age, gender, time since COVID-19 diagnosis, and self-reported fatigue (Beta = −0.158, 95% Confidence Interval − 0.242 to −0.074, p = 0.001). Conclusion: In this cohort, every day of LA/BR during acute COVID-19 illness was independently associated with subsequent lower grip strength of approximately 150 g. These results underscore the importance of early mobilization and discouraging bed rest in the acute phase of COVID-19. Patients who are isolating should be encouraged to maintain physical activity and muscle strength as part of a modified isolation-friendly rehabilitation programme.